A Comparative Analysis of Climate Change Framing in Nepali Newspapers - Geng, Yiqun; Wagle, Tej Prasad (Bodhi: An Interdisciplinary Journal, 2024)
Nepal, because of its specific topographical and geographical characteristics, is at the epicenter of vulnerability to the impacts of climate change. This study investigates the way three Nepali newspapers, namely Kantipur, Nagarik, and Nayapatrika Daily framed climate change from January 1, 2023, to December 31, 2023. The research provides a comprehensive approach to investigating the framing ways used by these newspapers, identifying and evaluating five prominent frames: environmental impact, humanitarian, policy, and governance, economic, and global justice. Through rigorous examination of chosen reports and articles from the required timeframe, the study indicates a noticeable trend in framing preferences among these three publications. Significantly, the results highlight the centrality of the Policy and Governance Frame as the main focus, which comprises more than half of the total coverage, then following the Environmental Impact Frame. The research presented here provides vital insight into each of the methods applied by media sources to convey climate change in Nepal. The study highlights the significance of using a diverse framing approach for addressing the many facets of this complicated issue, acknowledging the nation’s varied climate-related challenges. This research not only contributes to the scholarly knowledge regarding climate change communication but also has practical implications for professionals in the media, policymakers, and the general public. The need for a more varied and diverse framing approach is emphasized, showing the potential for more successful communication tactics that are tailored to Nepal’s particular context and challenges in the face of climate change.